Bone Health and Human Immunodeficiency Virus Infection. Issue 6 (1st April 2013) - Schafer, Jason J.; Manlangit, Kristine; Squires, Kathleen E.
<x xml:space="preserve">Abstract</x> Low bone mineral density is common among persons with human immunodeficiency virus (HIV) infection, and studies reporting increased fracture rates in this patient population are emerging. The causes of low bone mineral density, osteoporosis, and fractures in persons with HIV are likely multifactorial, involving traditional risk factors, HIV infection, and exposure to antiretroviral treatment. Specific antiretrovirals such as tenofovir may cause a greater loss of bone mineral density compared with other agents and have recently been linked to an increased risk for fracture. As a result, recent treatment guidelines suggest that clinicians consider avoiding tenofovir as initial therapy in postmenopausal women. Evaluating bone mineral density and vitamin D status in persons with HIV may be important steps in identifying those requiring pharmacotherapy; however, the appropriate timing for bone mineral density and vitamin D screening is uncertain, as is the appropriate method of replacing vitamin D in HIV‐positive patients who are deficient. Further study is necessary to definitively determine the approach to evaluating bone health and managing low bone mineral density and vitamin D deficiency in patients with HIV infection.